2016
DOI: 10.1039/c5em00533g
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium-uptake by aquatic and terrestrial organisms-distribution determined by laser ablation inductively coupled plasma mass spectrometry

Abstract: Gadolinium (Gd) based contrast agents (CA) are used to enhance magnetic resonance imaging. As a consequence of excretion by patients and insufficient elimination in wastewater treatment plants they are detected in high concentrations in surface water. At present, little is known about the uptake of these species by living organisms in aquatic systems. Therefore the uptake of gadolinium containing chelates by plants and animals grown in exposed water or on soil irrigated with exposed water was investigated. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…In the recent years the anthropogenic Gd pollution, especially in aquatic systems, became a topic of extensive research [33][34][35] . However, we doubt that the low concentrations of Gd in tap water could lead to the found accumulation in bone tissue; and given the likely subject's occupational history, the likelihood of presumable occupational exposure to elevated concentrations of gadolinium is remote.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years the anthropogenic Gd pollution, especially in aquatic systems, became a topic of extensive research [33][34][35] . However, we doubt that the low concentrations of Gd in tap water could lead to the found accumulation in bone tissue; and given the likely subject's occupational history, the likelihood of presumable occupational exposure to elevated concentrations of gadolinium is remote.…”
Section: Discussionmentioning
confidence: 99%
“…were first joined to the algae added as food, and therefore light REEs could have greater toxic effect by direct uptake from the media. On the other hand, Lingott et al (2016), in an experiment with daphnids exposed to Gd, suggested a greater Gd content related by algae ingestion added as food. Although LN-uptake routes for the rotifer should be further studied for a better interpretation of the obtained effect, these previous results indicated that the addition of algae as food could modify the availability of LN for the organisms and therefore results should be interpreted carefully.…”
Section: Lanthanide Multi-toxicitymentioning
confidence: 99%
“…The observed decrease in LN concentration was directly correlated with time exposure, and LN precipitation seems to take place at the start of the tests with a high decline of the LN amount remaining in the solution (Figure SI-3). Differences between measured concentrations at the beginning and at the end of the tests ( , therefore free ions often account for a small portion in natural water, although they have generally been found as the main predictors of LN toxicity (Tan et al, 2017;Lingott et al, 2016).…”
Section: Mediamentioning
confidence: 99%
“…Another important topic is how the fields irrigated by contaminated water and the animals drinking it are affected, since these could affect the human food chain. This has been studied by Lingoot et al (27) who found that Gd-based contrast agents may reach the human food chain both from plants growing in fields which are irrigated with contaminated surface water and from animals which drink the water.…”
Section: Food Chainmentioning
confidence: 99%